E. Coli Infections - Importance of Early Diagnosis and Efficient Treatment 2020
DOI: 10.5772/intechopen.93115
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Escherichia coli

Abstract: In the last decades, antimicrobial resistance has become a global threat to public health systems worldwide. Among those bacteria that pose the greatest threat to human health because of its growing resistance to antibiotics are the members of the Enterobacteriaceae family, particularly Escherichia coli and Klebsiella spp. Among the different antibiotic-resistant mechanisms developed by bacteria, the ones found in Enterobacteriaceae are more diverse than those in other families and include resistance to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 84 publications
1
24
1
1
Order By: Relevance
“…Their low sensitivity to cefoxitin can be due to the loss of membrane porins or by the production of a cephalosporinase (26). In general, sensitivity rates of Escherichia coli strains in this study were higher than those observed in developed countries (27), not only to tigecycline but also to fluoroquinolones, cyclins and trimethoprim-sulfamethoxazole. Indeed, antibiotic prescribing and use policy differs from country to country and is not well implemented in low and middle-income countries (28).…”
Section: Accepted Manuscriptcontrasting
confidence: 57%
“…Their low sensitivity to cefoxitin can be due to the loss of membrane porins or by the production of a cephalosporinase (26). In general, sensitivity rates of Escherichia coli strains in this study were higher than those observed in developed countries (27), not only to tigecycline but also to fluoroquinolones, cyclins and trimethoprim-sulfamethoxazole. Indeed, antibiotic prescribing and use policy differs from country to country and is not well implemented in low and middle-income countries (28).…”
Section: Accepted Manuscriptcontrasting
confidence: 57%
“…Shiga toxin-producing Escherichia coli (STEC) is a gram-negative and opportunistic bacterium and is a common inhabitant of the gastrointestinal tract of a wide variety of warm-blooded animals but may become pathogenic due to its easy dissemination in different ecosystems through the water, soil, food, and others [ 1 , 2 ]. In addition, it is also one of the world’s most studied bacteria and is arguably the best understood of all model microorganisms [ 3 ]. The gastrointestinal tract of ruminants, especially cattle and sheep, has been shown to act as a natural reservoir of STEC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, E. coli is one of the most important and leading causes of mastitis in cattle, from which the pathogen can easily be transmitted to consumers through milk and dairy products [2]. In this regard, due to the excessive use of antibiotics used to control these diseases, significant resistance to a wide range of antibiotics has developed in several E. coli strains [3,4]. For this reason, the presence of the multi-drug pathogens in foods of animal origin such as milk, meat, and poultry has dramatically increased in recent years [5].…”
Section: Introductionmentioning
confidence: 99%